AI INTEGRATION IN BANKING: ELEVATING COMPETITIVE ADVANTAGE - Fattakhova Munisa Abdukhamitovna (Journal Park Publishing, 2024)
The article is devoted to the development and application of AI in the financial market, including the definition of AI, its types, main AI technologies and trends in their development. It also discusses the use of AI in certain sectors of the financial market, the conditions for the development of AI technologies, and the possible risks of introducing AI by financial organizations. Special attention is paid to a review of global trends in AI regulation.
Keywords: artificial intelligence, financial markets, finance, digital technologies, digital platform, online services.